Dos excessos de arquitetura ao desaparecimento dos edifícios - Bruno Luiz Coutinho Santa Cecilia (2016)
This study refers to the built environment as a medium in which the experience of space - dwelling - occurs. Its main hypothesis is that architectural objects offer more barriers than necessary to mediate the phenomenon of dwelling, and that this excess affects both the individual experiencing of space and the social relations. Initially, we develop a theoretical and conceptual framework for discussion, from which emerge the notions of architectural void, habitability and conflict in architecture. Relating these concepts to the conspicuity modes of objects described by Martin Heidegger, we propose to distinguish the architectural barriers between necessary and contingent, characterizing the latter as potential obstacles to the free experiencing of space. Through some examples, we seek to demonstrate the conspicuity of contingent barriers, which produces conflicts in the relationship between subjects and architectural objects. It is argued that an architecture made only by necessary barriers would be more open to appropriation by their users. Then, we examine different situations in which architectural barriers become excessive, obstructing relations and blocking the actions of individuals in space. In the following sections, we discuss the barriers intended to provide protection against inclement weather, privacy control and delimitation of private territories that, although are indispensable to the habitability of the spaces, may provide social control and become conflictual when exacerbated. Through remarkable examples of architecture, we seek to demonstrate how this occurs. In the course of these discussions, emerges the argument that the conflictual character of some barriers stems from an exaggerated emphasis on the objectual dimension of architecture to the expense of its use value. Afterwards, is presented the idea of dissolution or disappearance of architecture as an autonomous object, relating it to the distinction between necessary and contingent barriers. Finally, we make some concluding remarks about this study and its applicability to architectural design practice and education, ending with some suggestions for future researches.